Salt-Tolerant Synechococcus elongatus UTEX 2973 Obtained via Engineering of Heterologous Synthesis of Compatible Solute Glucosylglycerol - Cui, Jinyu; Sun, Tao; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2021)
The recently isolated cyanobacterium Synechococcus elongatus UTEX 2973 (Syn2973) is characterized by a faster growth rate and greater tolerance to high temperature and high light, making it a good candidate chassis for autotrophic photosynthetic microbial cell factories. However, Syn2973 is sensitive to salt stress, making it urgently important to improve the salt tolerance of Syn2973 for future biotechnological applications. Glucosylglycerol, a compatible solute, plays an important role in resisting salt stress in moderate and marine halotolerant cyanobacteria. In this study, the salt tolerance of Syn2973 was successfully improved by introducing the glucosylglycerol (GG) biosynthetic pathway (OD750 improved by 24% at 60 h). In addition, the salt tolerance of Syn2973 was further enhanced by overexpressing the rate-limiting step of glycerol-3-phosphate dehydrogenase and downregulating the gene rfbA, which encodes UDP glucose pyrophosphorylase. Taken together, these results indicate that the growth of the end-point strain M-2522-GgpPS-drfbA was improved by 62% compared with the control strain M-pSI-pSII at 60 h under treatment with 0.5 M NaCl. Finally, a comparative metabolomic analysis between strains M-pSI-pSII and M-2522-GgpPS-drfbA was performed to characterize the carbon flux in the engineered M-2522-GgpPS-drfbA strain, and the results showed that more carbon flux was redirected from ADP-GLC to GG synthesis. This study provides important engineering strategies to improve salt tolerance and GG production in Syn2973 in the future.